Equacionamento e modelagem da bobina bifilar de tesla e proposta da sua utilização como um sensor biotelemétrico autorressonante - Miranda, Caio Marcelo de (2012)
Biotelemetry is an important technique with many applications in biomedical engineering and other areas. The size of the remote unit or sensor is a major challenge in this area, and, in most cases, a sensor is desired to be as small as possible. Thus, passive sensors are interesting because they allow a smaller dimensions and do not require a power source or battery, which can harm the patient in the event of leakage of its chemical content. Thus, the self-ressonant inductive sensor is a good solution since it can be built with only one component. Due to its small size, this type of sensor has a low stray capacitance, which makes its self-resonance frequency very high. In this case, the bifilar coil, devised by Nikola Tesla, can be a solution, since Tesla's idea was to increase the intrinsic capacitance of his coils. Therefore a physical understanding of the bifilar coil is necessary, since as far as is known, this approach does not exist in the literature. From an analysis of the voltage between adjacent turns, equations of the Tesla's bifilar coil were developed, allowing the prediction of the increase on the internal capacitance and consequent reduction of the resonance frequency. An equivalent electric model was also developed from this analysis. This allowed the project of bifilar coils and the calculation of the internal capacitances and self-resonance frequencies of these coils. Tests were realized in order to compare the calculated and measured self-resonance for various numbers of turns, showing the validity of the presented method. A passive self-resonant biotelemetric sensor for displacement measurement using the Tesla's bifilar coil, was also developed.